Relative efficiency of free fatty acid butyl esterification: choice of catalyst and derivatisation procedure - Hallman, Christian; Van Aarssen, Bernardus; Grice, Kliti (Elsevier, 2008)
The conversion efficiency of alkanoic, alkenoic, branched, alicyclic, aromatic, keto-substituted, and dioic carboxylic acids to their corresponding butyl esters was compared under different reaction conditions (time, temperature, catalyst). We show that boron trifluoride is generally a more efficient catalyst than sulphuric acid. However, optimum derivatisation conditions vary strongly for different acids and no single derivatisation protocol can be employed without certain losses. Therefore, care must be taken when the simultaneous quantitative analysis of different types of carboxylic acids in one sample is envisaged.Addition of water-scavenging reagents to the reaction mixture caused the formation of artefacts andselectively decreased reaction yields.